POLITIK UANG PEMILIHAN KEPALA DESA DALAM PERSPEKTIF MASYARAKAT TULUNGAGUNG - ., Muksin; ., Ladin (Ahkam: Jurnal Hukum Islam, 2023)
This research aims to find out and analyze community perceptions regarding the existence of money politics in village head elections and forms of money politics in village head elections. The research method used is an empirical research method consisting of primary data and secondary data. The research results of the two problems that the author examined are (1) Some people perceive that money politics or giving other goods in village head elections has become a habit that has occurred in Indonesia. (2) That there are various forms of money politics in society during village head elections, not only giving money, but also providing goods such as basic necessities and even giving school equipment which also occurs in the village head election process.